Elementos traço em tecido hepático de tartaruga-verde (Chelonia mydas) coletadas na Bacia de Santos, Brasil - Sulato, Everton Tiago [UNESP] (2020)
As, Cd, Cr, Cu, Pb, Mn, Mo, Zn, Ni, Ba V and Hg concentrations in liver tissue of green turtles (Chelonia mydas) stranded on the Brazilian coast (n=506) were determined. The data was compared to occurrence registers (date, location) and biological characteristics (sex, age, stage of development and curved carapace length). Possible temporal influence of oil exploration and production activities was assessed. The mean concentration of Cd, Cu, Mn, Zn and Hg were the highest reported in liver for C. mydas in Brazilian coast. The mean concentration of the elements in decreasing order was Cu> Zn> Cd> Mn> As> Hg> Mo> Pb> V> Ni> Ba> Cr. Significant difference between the sexes was observed for Hg (males > females). This difference had not been previously observed in Brazil. Significant differences (p < 0.05) were observed in the mean concentrations of As, Cu, Pb, Mo and V between specimens in their first years of life and aged ≥ 11 years, which suggests relation with dietary shift during development. These results were corroborated by curved carapace length (CCL) data, wherein individuals residing in coastal areas (CCL > 50 cm) presented higher concentrations for Cu, Pb, Mo, Zn, Ba and V when compared to the ones at the oceanic stage (CCL < 30 cm). The opposite pattern was observed for As and Hg. Spatial autocorrelation was not observed for element concentrations. In the present study, a baseline concentration of 12 trace elements was stablished for liver tissue of C. mydas juveniles in Santos Basin, Brazil, at 95% confidence level (As = 9 ± 10; Cd = 25 ± 18; Cr = 0.12 ± 0.10; Cu = 207 ± 125; Pb = 0.7 ± 1.0; Mn = 12 ± 4; Mo = 1.0 ± 0.6; Zn = 147 ± 50; Ni = 0.3 ± 0.4; Ba = 0.2 ± 0.3; V = 0.7 ± 0.9; Hg = 2 ± 22 mg kg-1). Influence of oil and natural gas production activities on the concentration of the elements could not be stablished. However, it was observed an expressive influence of the individual’s development stage, highly related to feeding habits, in the concentration of analyzed elements.